LABORATORY EVALUATION OF SOME NOVEL INSECTICIDES AGAINST AGROTIS SEGETUM (DENIS & SCHIFFERMULLER) FED ON POTATO LEAVES - Sharma, Nikhil; Verma, K S (Potato Journal, 2013)
Efficacy of six novel insecticides viz., bifenthrin, clothianidin, flubendiamide, indoxacarb, thiamethoxam and thiodicarb was evaluated through leaf dip method of bioassay against third and sixth instar larvae of agrotis segetum (Denis and Schiffermuller) under laboratory conditions. Amongst these, bifenthrin was found most effective with LC50 values of 0.009 and 0.089 ppm for the third and sixth instar larvae, respectively. Indoxacarb was second best with respective LC50 values of 0.040 and 0.476 ppm against the respective instars. When the relative toxicity of insecticides was calculated, bifenthrin was found to be about 521 times more toxic than thiamethoxam (least toxic insecticide) for the third instar larvae. While for the sixth instar it was about 299 times more toxic than thiodicarb (least toxic insecticide).